Structural Characteristics of the Turning End of the Kaiping Syncline and Its Influence on Coal Mine Gas - Zhenning Chen; Yanming Zhu; Hanyu Zhang; Jin Li (Applied Sciences)
Frequent coal mine gas disasters pose significant threats to the safety of miners and the continuity of coal mining operations. Understanding and mastering the patterns of gas occurrence is the foundation for controlling gas outbursts. This study, drawing on previous theories, research, and practical coal mine production data, analyzes the structural characteristics of the Kaiping syncline, with particular emphasis on the structural differentiation at its northeastern uplifted end. The study examines how gas generation and storage are influenced by progressively layered structures and their effect on coal mine gas management. The results indicate that the Kaiping syncline has a NE-SW axial orientation, which gradually shifts to an asymmetric syncline with a nearly EW trend, rising towards the northeastern end. At the turning end, the strata on the northwest limb are steep—locally vertical or overturned—gradually transitioning into the gentler southeast limb with dips of 10° to 30°, further complicated by a series of sub-parallel secondary folds. The gas formation process in coal seams has undergone multiple stages, regulated by structural burial and thermal evolution. The current gas storage characteristics result from the combined effects of these structural factors. The Kaiping syncline can be divided into two gas zones: a high-gas zone in the northwest limb and a shallow low-gas zone paired with a deep high-gas zone in the southeast limb. At the turning end, structural differentiation results in significant variations and gradations in the gas storage conditions of the coal seam. This differentiation directly causes a transition from coal and gas outburst mines in the northwest limb to low-gas mines in the southeast limb, highlighting the significant influence of structural factors on gas generation, preservation, and mine gas emissions. This study integrates theoretical analysis with measured data to enhance the understanding of structural evolution and its influence on gas storage. It offers guidance for preventing coal seam gas disasters and ensuring the safe production of coal mines in the Kaiping coalfield.